The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes - Bollino, Maurizio; Uliana, Marco; Sabatinelli, Guido (Zootaxa, 2019)
The present contribution revises the taxonomy of the Pygopleurus Motschulsky, 1860 species from the mainland Greece, introducing substantial changes to the last taxonomic work by Baraud (1989). Pygopleurus humeralis (Brullé, 1832) is recognized as a junior synonym of P. apicalis (Brullé, 1832). Specimens up to date identified as P. humeralis actually belong to five different taxa, of which two are new: P. brullei brullei Bollino, Uliana & Sabatinelli, new species and P. brullei taygetanus Bollino, Uliana & Sabatinelli, new subspecies, two are resurrected from synonymy: P. viridisuturatus (Reitter, 1903) from Greece, and P. isikdagensis (Petrovitz, 1963) from Turkey, and one species, P. bulgaricus (Nedelkov, 1905) is resurrected. Pygopleurus pseudopsilotrichius (Petrovitz, 1958) is resurrected from unwarranted synonymy with P. anemoninus (Brullé, 1832). Pygopleurus chrysonotus (Brullé, 1832) is removed from the synonymy with P. anemoninus and treated as senior synonym of Pygopleurus diffusus (Petrovitz, 1958). Pygopleurus anemoninus, P. chrysonotus and P. hirsutus (Brullé, 1832) are endemic to Greece, and absent from the fauna of Turkey. Previous records of these species from Turkey result from misidentifications. Neotypes of Pygopleurus chrysonotus and P. bulgaricus are designated. Neotype of Amphicoma apicalis designated by Baraud (1989) and lectotype of A. humeralis selected by Baraud (1989) in 1988 are considered invalid and set aside. For all species, ecological notes are presented and geographical distributions are mapped.